Percutaneous Coronary Intervention in Familial Hypercholesterolemia Is Understudied - Ungar, Leo; Sanders, David; Becerra, Brian; Barseghian, Ailin (Frontiers in Cardiovascular Medicine, 2018)
Familial hypercholesterolemia (FH) is a common heritable condition in which mutations of genes governing cholesterol metabolism result in elevated LDL levels and accelerated atherosclerosis. The treatment of FH focuses on lipid lowering drugs to decrease patients' cholesterol levels and reduce their risk of cardiovascular events. Even with optimal medical therapy, some FH patients will develop coronary atherosclerosis, suffer myocardial infarction, and require revascularization. Yet, the revascularization of FH patients has not been widely studied. Here we review FH, identify unanswered questions in the interventional management of FH patients, and explore barriers and opportunities for answering these questions. Further research is needed in this neglected but important topic in interventional cardiology.